The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10006-014-0449-2
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the maxilla related to long-standing methamphetamine abuse: a possible new aspect in the etiology of osteonecrosis of the jaw

Abstract: Two possible mechanisms, alone or in combination, could possibly lead to MA-related ONJ. Self-extraction of teeth as a psychopathologic behavior of self-destruction among MA abusers results in wounds that allow unhindered invasion of microorganisms causing osteomyelitis and ONJ, while on the other hand, the heating of white phosphor releases toxic phosphorous vapor, which could be inhaled and consequently cause ONJ of the maxilla. However, since the worldwide prevalence of MA abuse is remarkably high, a relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Rustemeyer et al, published a case report of a patient with an extended osteonecrosis of the maxilla after self-extraction of teeth and chronic methamphetamine abuse for 20 years. The authors concluded that (I) the self-extraction of the teeth in combination with bacterial wound contamination and (II) the inhalation of toxic phosphorus vapor, after heating white phosphor, might be responsible for ONJ development is this patient [ 26 ]. Hypothesis (II) is very interesting and might be a very relevant aspect since phosphor is an essential substitute for the illegal manufacture of “meth”.…”
Section: Discussionmentioning
confidence: 99%
“…Rustemeyer et al, published a case report of a patient with an extended osteonecrosis of the maxilla after self-extraction of teeth and chronic methamphetamine abuse for 20 years. The authors concluded that (I) the self-extraction of the teeth in combination with bacterial wound contamination and (II) the inhalation of toxic phosphorus vapor, after heating white phosphor, might be responsible for ONJ development is this patient [ 26 ]. Hypothesis (II) is very interesting and might be a very relevant aspect since phosphor is an essential substitute for the illegal manufacture of “meth”.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic use of recreational or illicit drugs such as cocaine, amphetamine and methamphetamine are established independent risk factors for osteonecrosis, termed Recreational drug induced osteonecrosis (RDIO) 29-32 . It is more common in the maxilla 29 .…”
Section: Types Of Osteonecrosismentioning
confidence: 99%
“…It is more common in the maxilla 29 . The incidence of recreational drug induced osteonecrosis is unknown because many addicts do not seek medical care.…”
Section: Types Of Osteonecrosismentioning
confidence: 99%
“…Кроме того, эти вещества применяются в онкологии для терапии костных метастазов, сочетающихся с синдромом гиперкальциемии. Однако известно, что эти препараты могут вызывать тяжелые осложнения остеонекрозы челюстей [1,2,3]. Подобные процессы исследователи наблюдают у лиц, употребляющих метамфетамин кустарного производства, при изготовлении, которого применяется красный фосфор.…”
Section: Introductionunclassified